Profil moluskum kontagiosum di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2013-Desember 2015 - Runtuwene, Nadya; Niode, Nurdjannah; Pandaleke, Thigita (e-CliniC, 2016)
Abstract: Molluscum contagiosum is an infection disease of the skin caused by Molluscipox virus. This disease is transmitted through direct and indirect contact, such as the use of personal goods together. This disease primarily affects children and actively sexual adult. The world highest prevalence of mollucum contagiosum was reported in East Afrika, as much as 52%. In Indonesia, the prevalence is high, around 40.4% of all skin diseases. This is a descriptive study, with the retrospective approach. The aim of this study is to investigate the prevalence of molluscum contagiosum. The study population is all new patients who come to the outpatient clinic of dermatology and venereology Prof. Dr. R. D. Kandou Hospital, Manado. The study sample is all new patients diagnosed with molluscum contagiosum. This study found that, from 2013-2015 periods, a total of 60 patients (1.66%) were diagnosed with molluscum contagiosum. This infection is likely to be found in men (31 patients; 51.7%), 5-14 years old age group (38; 63.3%), and students (29 patients; 48.3%). The location is likely to be in a combination of facial, thorax, and extremities (34 patients: 56.7%). Most of the patients were treated with curettage (56 patients; 93.3%). Based on the study findings, the author suggested to give education to the general public, especially the parents, so the curative, preventive, and promotive efforts can be done well.Keywords: molluscum contagiosum, children, curettageÂ Abstrak: Moluskum kontagiosum adalah sebuah penyakit infeksi kulit yang disebabkan oleh virus Molluscipox. Penularannya dapat melalui kontak langsung dan tidak langsung seperti pemakaian alat-alat pribadi bersama. Penyakit ini terutama menyerang anak-anak dan dewasa dengan aktivitas seksual aktif. Di dunia prevalensi moluskum tertinggi terdapat di Afrika Timur sebesar 52%. Di Indonesia prevalensi moluskum kontagiosum tergolong tinggi, yaitu sebesar 40,4% dari penyakit kulit lain. Penelitian ini bersifat deskriptif dengan cara retrospektif yang bertujuan untuk mengetahui profil moluskum kontagiosum. Populasi pada penelitian adalah seluruh data pasien baru yang berobat di poliklinik kulit dan kelamin RSUP Prof. Dr. R. D. Kandou Manado, sampel yang diambil adalah semua pasien baru yang didiagnosis moluskum kontagiosum. Dari hasil penelitian tahun 2013-2015 didapatkan total pasien moluskum 60 (1,66%), terbanyak pada laki-laki 31 (51,7%) pasien, usia 5-14 tahun kelompok umur terbanyak 38 (63,3%) pasien, terbanyak di kalangan pelajar 29 (48,3%) pasien, lokasi kombinasi dari fasial, thoraks, dan ekstremitas paling banyak terkena dengan jumlah 34 (56,7%) pasien, dan terapi yang sering digunakan yaitu kuretase yaitu 56 (93,3%) pasien. Dari hasil yang ditemukan salah satu saran adalah dengan memberikan edukasi pada masyarakat luas, terutama pada orang tua agar upaya kuratif, preventif, dan promotif, dapat terlaksana dengan baik. Kata kunci: moluskum kontagiosum, penyakit infeksi kulit, kuretase